A Pharmacognostical Comparative Investigation on Valeriana alliariifolia_x000D_ Adams - (:unkn) unknown (My University, 2020)
Free radicals are shown as the main reason of many chronic anddegenerative diseases. Because of the toxicity and undesirable effects ofsynthetic antioxidants, finding of new antioxidant natural agents is veryimportant, especially edible plants. As an edible plant, valerian is used forvarious aims. Also, Valeriana species are known with their antioxidativecompounds. In our previous study, some biological activities of Valerianaalliariifolia Adams roots extracts, collected in 2012, and the chemicalcompositions of active samples were determined. For this study, after 5 yearscollected plant materials were investigated again to determine and compare theantioxidant activities, the total phenolic contents and the chemical compositionprofile of the extracts from different plant-parts and to compare obtained resultswith the previous data. While RWI, RWM1 and RWM1residue were foundmost active by DPPH method and AHM1 by FRAP method, REM1 showedthe highest activity by CUPRAC method. The high activity of AHM1 is parallelto its phenolic content. It can be thought that the difference between the resultsof our two studies, is due to the change of plant content from year to year andvarious environmental factors. This is important for achieving standardizationin the production of its preparations.